Suppression of additive periodic low-frequency interference on eddy current defectograms - Leonid Y. Bystrov; Artemy N. Gladkov; Egor V. Kuzmin (Моделирование и анализ информационных систем)
Traffic safety in railway transport requires regular inspection of the rail condition to identify and timely eliminate defects. Eddy current flaw detection is one of the popular methods of non-destructive rail testing. The data (defectograms) obtained from eddy current flaw detectors during rail testing are produced in large volume and therefore need in efficient automatic analysis. The analysis means the process of detecting on defectograms the presence of defective areas and identification of structural elements of the rail track, taking into account noise and possible interferences of various natures. The threshold noise level is found to isolate signals from defects and structural elements. Its value can be distorted by electromagnetic influences superimposed on the signals, which have pronounced low frequency and periodicity. This interferences raises the threshold noise level, complicating to detect useful signals. In this regard, there is a need to suppress the effects of the described type. Therefore, there is a need for described interferences reduction. In this paper spectral subtraction was used as a method for interference reduction on eddy current defectograms. The interference function was defined as the sum of the low-frequency harmonics of the Discrete Fourier Transform of the original signal. Then the interference-free signal can be found by subtracting of low-frequency range harmonics. The right boundary of this range was called the threshold harmonic frequency. It was found minimizing the distance of the signal's autocorrelation function and expected autocorrelation. For it two kinds were proposed: the noise autocorrelation and the reference autocorrelation. Both approaches allow to determine the threshold harmonic frequency so that periodic interferences will be best reduced. The based on the Gaussian noise autocorrelation method is somewhat universal for eddy current defectograms. Whereas the based on reference autocorrelation method depends on specific data and recording equipment. For the eddy current defectogram data under consideration, the most suitable threshold harmonic frequency was found. The described approaches to periodic low-frequency interference reduction, in addition to eddy current testing, can be successfully used for other areas.